Implementation of Infection Prevention and Control Management in Health Workers at Unimus Dental and Oral Hospita - Sholekhah, Nur Khamilatusy; Ayudyawati, Melinda Savira; Arti, Dwi Windu Kinanti (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Hospitals as health care facilities are prone to infection. Infections that occur in hospitals are called nosocomial infections or can be called HAIs (Healthcare Associated Infection). Various kinds of procedures and dental health facilities can potentially cause infection transmission. There are infection prevention and control guidelines issued by the Ministry of Health in 2017, but their implementation is still not optimal. One of the factors that influence the implementation of infection prevention and control is the lack of awareness in complying with and understanding the guidelines. To describe the implementation of infection prevention and control in health workers at Unimus Dental dan Oral Hospital. The type of research used is analytic observational with a cross sectional research design through a descriptive approach. Results: 94.9% of dental professional students were very good at implementing infection prevention and control, but 2.6% were still lacking. As many as 71.4% of dentists are good at implementing infection prevention and control, but 14.3% are still lacking. 50% of dental nurses are very good at implementing infection prevention and control. And 100% of the PPI staff have been very good at implementing infection prevention and control at Unimus Dental dan Oral Hospital. The implementation of infection prevention and control in the Unimus Dental dan Oral Hospital for students of professions, PPI staff, dentists, dentists and dental nurses, the results were 87.7% very good, 7% good and 5.3% not good